Decrease in domestic petroleum prices on Malaysian industries - input output price model - Abdullah Chik, Norlaila; Saari, Mohd Yusof; Utit, Chakrin (Global Advanced Research Journals, 2017)
This paper examines the impact of the decrease of petroleum product prices on sectoral cost of production in Malaysia. By using the Leontief price modelling technique, a scenario for the price changes on sectoral costs of production were simulated. The simulation results indicated that a five percent decrease in petroleum prices will affect all economic sectors. The cost of production for certain sectors, such as air transport, fishing, land transport, cement, lime and plaster, as well as communications are estimated to experience the lowest of production costs. Based on this scenario, the government has to encourage producers or sellers to reduce their prices of goods and services.